AKUNTABILITAS KINERJA INSTANSI PEMERINTAH ACEH DAN FAKTOR YANG MEMPENGARUHINYA - Lestari, Putri Ayu; Aliamin, Aliamin (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This study aims to determine the effect of budget target clarity, accounting control, and reporting systems on performance accountability in Aceh government agencies. The population in the study were state civil servants at the Aceh Financial Management Agency who carried out their activities in the programming or planning subdivision for young experts, the finance subdivision, the revenue sector, the Aceh Budget sector, the Aceh Property Management sector, the treasury sector, the accounting sector, the development sector, and the district city budget evaluation, with a population of 125 respondents. The sample used was simple random sampling with the Slovin formula, with 55 respondents as the research sample. The results showed that the clarity of budget targets and accounting controls partially had no significant effect on performance accountability, while the reporting system affected performance accountability. In addition, the clarity of budget targets, accounting controls, and the reporting system influence performance accountability in Aceh government agencies simultaneously.